A gamificação no ensino de astronomia nos anos finais e na EJA do Ensino Fundamental: uma estratégia para a aprendizagem significativa - Espedito, Fabrício Luís de Carvalho (2021)
The teaching of Astronomy in Geography in the Final Years of Elementary School presents obstacles that hinder meaningful learning. The search for the construction of resources that promote contextualized and science-based learning guides this work. Gamification as an active methodology aims to contribute through game mechanics to meaningful learning, associating the knowledge of astronomy with the scientific and technological development of mankind, collaborating with the development of student learning through motivation and engagement. The integration of knowledge in astronomy in curriculum components is recommended in the BNCC that gives status of interdisciplinary science with relevant interaction with various areas of knowledge, this range of possibilities has in Gamification a resource of great value to assist in the knowledge of students. The mosaic of realities and ages of students who participated in the work, ranging from 6th grade to Youth and Adult Education provided understanding of how Gamification interferes positively in learning even with the huge variation of age groups, thus points to the relevance of this resource included in active methodologies as a support for the development of student protagonism in their learning. The development of the educational product Astronomical Dominoes was based on the thought of collaborating effectively with the development of meaningful learning of students associating Astronomy and Geography, collaborating in the understanding of phenomena and aspects related to the stars of the Solar System.